Elemental and Isotopic Fingerprint of Argentinean Wheat. Matching Soil, Water, and Crop Composition to Differentiate Provenance - Podio, Natalia Soledad (2013)
The aim of this study was to investigate if elemental and isotopic signatures of Argentinean wheat can be used to develop a reliable fingerprint to assess its geographical provenance. For this pilot study we used wheat cultivated at three different regions (Buenos Aires, Córdoba, and Entre Ríos), together with matching soil and water. Elemental composition was determined by ICP-MS. δ13C and δ15N were measured by isotopic ratio mass spectrometry, while 87Sr/86Sr ratio was determined using thermal ionization mass spectrometry. Wheat samples from three sampling sites were differentiated by the combination of 11 key variables (K/Rb, Ca/Sr, Ba, 87Sr/86Sr, Co, Mo, Zn, Mn, Eu, δ13C, and Na), demonstrating differences among the three studied regions. The application of generalized Procrustes analysis showed 99.2% consensus between cultivation soil, irrigation water, and wheat samples, in addition to clear differences between studied areas. Furthermore, canonical correlation analysis showed significant correlation between the elemental and isotopic profiles of wheat and those corresponding to both soil and water (r2 = 0.97, p < 0.001 and r2 = 0.96, p < 0.001, respectively). To our knowledge, this is the first report demonstrating the correspondence between soil, water, and wheat samples using different statistical methods, showing that wheat elemental and isotopic compositions are mainly related to soil and irrigation water characteristics of the site of growth.